O processo de colonização e os conflitos agrários na região de Urupá/RO (décadas de 1970 e 1980) - Oliveira, Vicência Guedes de (2024)
This research presents an analysis of the process of reoccupation and colonization in Rondônia, as well as specifically the process of colonization and reoccupation in the region of the current municipality of Urupá/RO, in the 1970s and 1980s, encouraged by the military dictatorship through programs to reoccupy and integrate the Amazon. Thus, many people, mainly from the South, Northeast and Southeast of the country, migrated to Urupá and other regions of Rondônia in search of new opportunities and better living conditions. Most of these migrants were farmers, adventurers, rubber tappers, cattle ranchers, loggers and miners. Migration to Urupá and other Amazonian regions also brought social and environmental problems, such as deforestation, agrarian conflicts and the exploitation of natural resources without proper management. Consequently, the process of reoccupation and colonization generated conflicts between squatters, rubber tappers, farmers, ranchers and indigenous people. These land disputes are still a major issue in the state. Therefore, the main objective of this research is to analyse aspects of the reoccupation and colonization process and the agrarian conflicts that took place in Urupá in the 1970s and 1980s. The main sources of research used were bibliographical sources and oral history through interviews. Five people were interviewed: a representative of social movements, a rubber tapper, an indigenous leader from the Amondawa Reserve and two representatives of the colonizers. In this way, we will try to contextualize the process of reoccupation and colonization of Rondônia from the 19th century onwards, from the plant and mineral extraction phase, through the construction of the Madeira-Mamoré Railway (EFMM) and the Telegraph Lines by the Rondon Commission, to the programs for the occupation and integration of the Amazon, implemented by the military dictatorship from the 1970s onwards. We also sought to analyze the process of reoccupation and colonization in the Urupá region in the 1970s and 1980s, as well as the agrarian conflicts that resulted from this process.